Middle managers’ role in organizational commitment and organizational citizenship behaviours - Landa, Clive H. (Cranfield University, 2015)
“Any motivated behavior, either preparatory or consummatory, must be understood to be a channel through which many basic needs may be simultaneously expressed or satisfied. Typically an act has more than one motivation.” (Maslow 1943, p.370) Written before organizational behaviour had been named let alone studied as a separate discipline, Abraham Maslow warned of the dangers of assuming that an individual behaviour can be explained simply by a single motivation. This dissertation will argue that where organizations operate in the context of continuing downsizing over long periods it is necessary to consider more than just positive affect employee motivations, such as organizational commitment. It may also prove important to consider more ambivalent motivations such as those involved in impression management. Since the early days of organizational behaviour researchers have sought to explain the degree of attachment shown by workers towards their organization. A great deal has been learned regarding two related constructs, organizational commitment and organizational citizenship behaviours. This research contributes to the theoretical framework underlying these two constructs. Empirical studies have shown associations between organizational commitment and aspects of an organization’s culture, for example organizational values and vision/mission. The underlying process has been explained by use of social exchange theory (Blau, 1964). Similarly, studies have shown an association between organizational citizenship behaviours and two other constructs besides organizational commitment, the individual’s perception of support from the organization and from the individual’s manager respectively. The resulting, widely accepted, models explain citizenship behaviours through two ‘pathways’, one via support from the organization, the other via support from their manager. Provision of such support is met by positive reciprocation by the individual. The research reported here assumes that any relationship between an individual employee and their organization may, and is likely to, be influenced by the actions of their direct report manager. A systematic literature review showed comparatively little research into the role of the manager and his/her role in influencing organizational commitment. This led to two empirical studies of middle managers’ role in influencing organizational commitment in their teams. Throughout this thesis the term middle manager is used interchangeably with direct report manager or line-manager. These terms are expressly taken to exclude both senior managers (those in a position to determine or contribute significantly to organizational level factors e.g. vision/mission and HR policies) and the first line supervisor with only task and team leader responsibilities. The first study found that the managers in the sample preferred the term engagement to commitment and that they focused largely on those citizenship behaviours of their direct reports that contributed directly to major performance measures i.e. key performance indicators. The second study in a different organization set out to explore whether or not this finding was repeated and irrespective of this, what techniques if any the managers used to influence both organizational commitment and citizenship behaviours in their teams. In addition to repeating the use of qualitative methods this study also incorporated some quantitative methods (surveys) in order to identify the direct reports’ levels of the relevant constructs. While the survey results showed that levels of both commitment and citizenship were high, unexpectedly and contrary to current models, the levels of perceived organizational and manager support were low. This runs counter to the prediction of social exchange theory. Nevertheless, it is argued that the current data can be explained, if one adds a third pathway to the model via impression management. This in turn can be attributed to an individual’s heightened job insecurity in times of downsizing and a consequent attempt to demonstrate one’s value to the manager/organization. It is further argued that any citizenship behaviours that may arise from impression management may not fully exploit the potential contributions from individuals. The techniques used by middle managers to encourage both organizational commitment and citizenship behaviours in their teams are reported and suggestions for further research are discussed.